The Influence of Gender and Training Sector on the ICT Competency of Pre-Service Teachers in Vietnam: Using the UNESCO ICT Competency Framework - Thao, Trinh Thi Phuong; Thi-Nga, Hoang; Hang, Nguyen Thi Thu; Thai, Doan Thi Minh; Linh, Ha Thi Kim; Nhung, Nguyen Do Hong; Giang, Nguyen Do Huong; Dinh, Ngo Van (International Journal of Learning, Teaching and Educational Research, 2024)
Information and communication technology (ICT) is a powerful educational change and reform tool. Teachers are a direct subject in promoting the application of information technology (IT), and the ability to integrate technology into teaching affects the application of IT in teaching. Integrating ICT into education requires teachers to be competent in using ICT. In other words, teachers are required to have sufficient ICT competence to use ICT for education. Faced with this requirement, teacher training schools have made positive changes to improve the ICT capacity of pedagogy students and prepare graduates to perform their duties in the context of digital transformation in education today. This study collected information on pre-service teachers’ competency in using ICT as future teachers in Vietnam. Using the ICT competency framework of UNESCO, the research surveyed 1698 fourth year teaching students (pre-service teachers) from 10 provinces in 3 regions of Vietnam. The results indicate that although pre-service teachers in Vietnam are well educated on ICT policy issues in education, for the issue of ICT exploitation to support curriculum implementation and assessment, they still need ICT skills to support effective teaching and learning methods. In addition, there are significant differences in gender and training specialization in some aspects, such as the application of digital skills and the use of ICT in organization and administration. These results are the basis for in-depth research into establishing influencing factors and measures to improve the ICT application competency of pre-service teachers, contributing to ensuring the quality of education in Vietnam. https://doi.org/10.26803/ijlter.23.3.20